Application of the Naive Bayes Method in Predicting the Level of Community Satisfaction with the Performance of the Magho Linyo Village Head - Seselia Soli Lede; Gergorius Kopong Pati; Alexander Adis (Jurnal Penelitian Teknologi Informasi dan Sains, 2024)
Village monies are sourced from the State Budget (APBN) and are allocated in accordance with Law Number 6 of 2016 for the purposes of development, coaching, social activities, and community empowerment. The existence of village finances is necessary to support all sources of revenue for the village, and as the government's revenue grows, so too must the village's public service infrastructure. As a result, the sentiment analysis of village officials will be done in this study. The analysis will include the classification of community sentiment using the Naive Bayes technique. To assess each method's accuracy, two will be contrasted. The village administration, as the highest social institution in the community, is crucial in establishing norms, distributing funds, and creating a help-related socialization process. Furthermore, some Pada Eweta village inhabitants may not receive help, which may cause social rivalry amongst locals. Sentiment categorization will be used to classify responses as positive or negative. Based on feedback from visitors, this study seeks to evaluate the validity of the two approaches put to the test and provide insight into the level of service provided by village officials. The accuracy of both methods will be verified by evaluating the outcomes with the RapidMiner tool.